The Effectiveness of Digital Interactive Media Worksheets in Improving Elementary School Students’ Mathematical Literacy - Isna Amaliya; Aida Suraya; Sumaji; Sri Utaminingsih; Pratama, Hendri (Studies in Technology and Education, 2024)
This study aims to develop interactive digital worksheet media to enhance the mathematical literacy skills of elementary school students. The Research and Development method, based on Sugiyono's model, was employed, encompassing potential and problem identification, data collection, product design, design validation, product revision, product testing, and final product revision. The study involved teachers and fourth-grade students at SDN Mangunjiwan 1 Demak. The results indicate that the interactive digital worksheets are highly valid, with an average validation score of 89.31%. Effectiveness testing showed a significant improvement in mathematical literacy skills, with the experimental class achieving an average N-Gain score of 83.33%, categorized as very effective. Thus, interactive digital worksheets are highly effective in improving the mathematical literacy skills of fourth-grade students.